Bouncing-to-wetting transition of water droplets impacting soft solids. Issue 24 (28th May 2021) - Mitra, Surjyasish; Vo, Quoc; Tran, Tuan
Abstract : The bouncing-to-wetting transition of water droplets impacting PDMS-coated substrates was investigated. It was found that such transitions are dictated by a dimple inversion phenomenon. Abstract : Soft surfaces impacted by liquid droplets trap more air underneath than their rigid counterparts. The extended lifetime of the air film not only facilitates bouncing behaviours of the impacting droplets but also increases the possibility of interactions between the air film itself and the air cavity formed inside the droplets by capillary waves. Such interactions may cause rupture of the trapped air film by a so-called dimple inversion phenomenon and suppress bouncing. In this work, we systematically investigate the relationship between air cavity collapse and air film rupture for water droplets impacting soft, hydrophobic surfaces. By constructing a bouncing-to-wetting phase diagram based on the rupturing dynamics of the trapped air film, we observe that the regime in which air film rupture is induced by dimple inversion consistently separates the bouncing regime and the one in which wetting is caused by random rupture. We also found that air film rupture by dimple inversion in-turn affects both the collapsing dynamics of the air cavity and the resulting high-speed jet. We then provide a detailed characterisation of the collapsing dynamics of the air cavity and subsequent jetting.